2011
DOI: 10.3109/11038128.2011.583939
|View full text |Cite
|
Sign up to set email alerts
|

Professional confidence: A concept analysis

Abstract: Developing and fostering professional confidence should be nurtured and valued to the same extent as professional competence, as the former underpins the latter, and both are linked to professional identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 43 publications
4
83
0
4
Order By: Relevance
“…One article on the conceptions of the professional confidence of eight CS occupational therapists in KwaZulu Natal 43 , although not directly relevant to this study, provided helpful background information. The article reported that CS occupational therapists in KwaZulu Natal were either sole-practitioners or worked in a small team of occupational therapists and sometimes alongside other CS rehabilitation staff.…”
Section: Introductionmentioning
confidence: 99%
“…One article on the conceptions of the professional confidence of eight CS occupational therapists in KwaZulu Natal 43 , although not directly relevant to this study, provided helpful background information. The article reported that CS occupational therapists in KwaZulu Natal were either sole-practitioners or worked in a small team of occupational therapists and sometimes alongside other CS rehabilitation staff.…”
Section: Introductionmentioning
confidence: 99%
“…Holland et al 19 . describe professional confidence as a dynamic, maturing personal belief held by a professional or student.…”
Section: Anticipated Future Action Cyclesmentioning
confidence: 99%
“…Developing and fostering professional confidence should be nurtured and valued to the same extent as professional competence, as the former underpins the latter, and both are linked to professional identity 19,20 . The teaching of structured writing, like report-writing, is important as a means of teaching therapists and students how to express and present information effectively, but also to facilitate scientific thinking 21,22 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selfesteem includes self-confidence, being a part of a broader self-concept (Gecas, 1982), while self-efficacy is narrower and refers to a person's certainty with regard to his/her own capabilities and competency in task execution. The terms of "confidence", "self-confidence", "professional confidence" and "self-efficacy" were defined as "surrogate" and were used as synonyms by the researchers (Holland et al, 2012). …”
Section: Personal Self-confidence and Its Componentsmentioning
confidence: 99%
“…In addition, it is linked to the concepts of self-efficacy and self-esteem (Caprara et al, 2003;Klassen & Chiu, 2010;Peng, Schaubroeck & Xie, 2015). However, very few studies were focused on conceptualizing the term of self-confidence (Shrauger & Schohn, 1995;Holland, Middleton & Uys, 2012), and less in known about the professional self-confidence of teachers and its components. In addition, the investigation and measurement of teachers' professional self-confidence of Lithuanian, Ukrainian and Finnish teachers have not been performed before.…”
Section: Introductionmentioning
confidence: 99%